Perencanaan Manajemen Lanskap Zonasi Destinasi Wisata Budaya Kota Tua Jakarta - Aryanto, Rudy; So, Idris Gautama (Binus Business Review, 2012)
Kota Tua is just like other historical old towns in various cities in developing countries, generally preserved even put to improve simultaneously historic and economic value of sustainable revitalization program which involves all stakeholders. The historical value and the architecture of the Kota Tua Jakarta are no less attractive compred to other cities in the world. Thus, Kota Tua has become a historical mainstay tourism destination objects for Jakarta and has broad potential to bring a lot of domestic and foreign tourists. Study on this research describes the identification of direction of planning and development of landscape management in historical tourism destinations of Kota Tua Jakarta. After conducting various studies and literature, then the spatial obtained existing condition, studies the potential of historical tourism, studies history, typology and building reserves, cultural space and Setup zoning patterns, which can be used for consideration and direction for management zoning landscape historical tourism in Kota Tua Jakarta.